Increased Plasma Level of 24S-Hydroxycholesterol and Polymorphism of CYP46A1 SNP (rs754203) Are Associated With Mild Cognitive Impairment in Patients With Type 2 Diabetes - Shi, Jijing; Jia, Jianhong; Tian, Sai; Zhang, Haoqiang; An, Ke; Zhu, Wenwen; Cao, Wuyou; Yuan, Yang; Wang, Shaohua (Frontiers in Aging Neuroscience, 2021)
Background: Abnormal cholesterol metabolism is common in type 2 diabetes mellitus (T2DM) and causes dementia. Cholesterol 24S-hydroxylase (CYP46A1) converts cholesterol into 24S-hydroxycholesterol (24-OHC) and maintains cholesterol homeostasis in the brain. Objective: This study aimed to investigate the roles of 24-OHC and the CYP46A1 (rs754203) polymorphism in patients with T2DM and mild cognitive impairment (MCI). Methods: A total of 193 Chinese patients with T2DM were recruited into two groups according to the Montreal Cognitive Assessment (MoCA). Demographic and clinical data were collected, and neuropsychological tests were conducted. ELISA and Seqnome method were used to detect the concentration of plasma 24-OHC and the CYP46A1 rs754203 genotype, respectively. Results: Compared with 118 healthy cognition participants, patients with MCI (n=75) displayed higher plasma level of 24-OHC and total cholesterol concentration (all p=0.031), while no correlation was found between them. In the overall diabetes population, the plasma level of 24-OHC was negatively correlated with MoCA (r=−0.150, p=0.039), and it was further proved to be an independent risk factor of diabetic MCI (OR=1.848, p=0.001). Additionally, patients with MCI and the CC genotype of CYP46A1 rs754203 showed the highest plasma level of 24-OHC even though the difference was not statistically significant, and they obtained low scores in both verbal fluency test and Stroop color word test A (p=0.008 and p=0.029, respectively). Conclusion: In patients with T2DM, high plasma level of 24-OHC and the CC genotype carrier of CYP46A1 rs754203 may portend a high risk of developing early cognitive impairment, including attention and executive deficits.